2017
DOI: 10.1016/j.ijpp.2016.11.001
|View full text |Cite
|
Sign up to set email alerts
|

A probable case of Legg-Calvé-Perthes disease in Warring States-era China

Abstract: Reports of Legg-Calvé-Perthes disease (LCPD) in the paleopathological literature are rare. Here, the authors present a probable case of LCPD, which presents as abnormal morphology of the proximal femur. The condition was observed in an individual of the Warring States period in Shaanxi Province, China, and the morphology involves a "mushroom head" deformity of the proximal right femur and an enlarged acetabulum, along with a contralateral tibia, talus, and navicular that are enlarged and demonstrate periosteal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…Generally, the paleopathological evidence of LCPD are scarce. The disease has been previously described in: Peru (Ortner and Putchar 1981;Ortner 2003), Majorca (Marques and Cunha 2001), Serbia (Đurić et al 2004), Czech Republic (Smrcka et al 2009), Portugal (Ferreira et al 2013, Argentina (Ponce and Novellino 2014), Egypt (Fritsch et al 2015), China (Berger et al 2017) and Spain (Manzon et al 2017). Our study provides the first case of LCPD described in bioarchaeological materials from Poland.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Generally, the paleopathological evidence of LCPD are scarce. The disease has been previously described in: Peru (Ortner and Putchar 1981;Ortner 2003), Majorca (Marques and Cunha 2001), Serbia (Đurić et al 2004), Czech Republic (Smrcka et al 2009), Portugal (Ferreira et al 2013, Argentina (Ponce and Novellino 2014), Egypt (Fritsch et al 2015), China (Berger et al 2017) and Spain (Manzon et al 2017). Our study provides the first case of LCPD described in bioarchaeological materials from Poland.…”
Section: Discussionsupporting
confidence: 60%
“…Similar to our sample pathologies has also been identified in ancient Egyptian mummies from the Museum of Antiquities in Cairo by Fritsch et al (2015), who examined orthopaedic diseases in Ancient Egypt, and by Manzon et al (2017) who reported on morphometric and radiological analyses of a skeleton from the Etruscan necropolis of Spina (Ferrara, Italy, 6 th -3 rd century BCE). Similarly, Berger et al (2017) examined skeletal remains of an individual from the Warring States period in Shaanxi Province (China), and observed a "mushroom head" deformity of the proximal right femur, an enlarged acetabulum, along with a contralateral tibia, talus as well as enlarged navicular with periosteal new bone formation. These conditions were also connected with LCPD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, B8.1's skeleton is consistent with a female, and pubescent girls are less likely than boys to suffer from SCFE because of the action of oestrogen against growth hormone (Jingushi & Suenaga, ). However, because SCFE can also manifest in a flattening of the femoral head similar to the observed mushroom defect (Berger, Chen, Sun, & Sun, ), it cannot be entirely ruled out.…”
Section: Resultsmentioning
confidence: 96%